Understanding teachers' emotional trajectory: the voice of a volunteer teacher in an educationally and economically underdeveloped context. Issue 2 (15th March 2021) - Zhang, Xiaodong
ABSTRACT: This qualitative case study explores one college teacher's emotional trajectory during volunteer teaching in a constrained (i.e., educationally and economically underdeveloped) context. The study shows that the teacher's emotions were continually shaped by external and internal factors over an academic year. The volunteer teacher's self-agency gradually emerged as a vital internal factor in regulating his fluctuating emotions and demonstrating his positive emotions for teaching. Additionally, while the teacher's emotions were generally expressed in a positive manner, in-the-moment emotions were also expressed negatively to galvanise students' learning.